2012
DOI: 10.1017/s0022215112001661
|View full text |Cite
|
Sign up to set email alerts
|

Utilising silk fibroin membranes as scaffolds for the growth of tympanic membrane keratinocytes, and application to myringoplasty surgery

Abstract: The properties of silk fibroin make it an attractive option for further research, as a potential alternative graft in myringoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Following the removal of sericin, an antigenic glue‐like coating protein, the core silk fibroin fibers are biocompatible with little immune response postimplantation . Previous studies demonstrated that silk fibroin could support cell adhesion, proliferation, and differentiation in vitro, including human TM keratinocytes . We recently reported hearing and healing benefits of silk fibroin membranes using onlay myringoplasty in rats, with improved structural outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the removal of sericin, an antigenic glue‐like coating protein, the core silk fibroin fibers are biocompatible with little immune response postimplantation . Previous studies demonstrated that silk fibroin could support cell adhesion, proliferation, and differentiation in vitro, including human TM keratinocytes . We recently reported hearing and healing benefits of silk fibroin membranes using onlay myringoplasty in rats, with improved structural outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown its efficacy to promote wound healing of skin, ligament, nerves, and bone . Our group has demonstrated that silk fibroin can successfully support human TM cells in vitro . Collagen has been widely used as a bioscaffold due to its biocompatibility and ability to promote the growth of many types of cells and tissues .…”
Section: Introductionmentioning
confidence: 96%
“…SF is rich in β‐sheet structures owing to hydrophobic domains which provide a good resistance to water solubility, and lead to the high mechanical properties of these materials . SF can be processed into fibers, membranes, films, meshes, foams, and hydrogels for the repair/regeneration of several tissues.…”
Section: Natural Polymers and Calcium Phosphate Materials Propertiesmentioning
confidence: 99%
“…Silk fibroin materials have effective mechanical properties for TM tissue engineering (21) and provide a suitable substrate for human TM keratinocytes (18). In order to test whether these TM cells would support a tissue-engineering approach, we cultured explant-derived cells on porous silk membrane scaffolds (Supplementary Figure S3A).…”
Section: Resultsmentioning
confidence: 99%